Association with subjective measured physical activity (GPAQ) and quality of life (WHOQoL-BREF) of ageing adults in Hungary, a cross-sectional study - Erzsébet Rétsági; Viktória Prémusz; Alexandra Makai; Csaba Melczer; József Betlehem; Kinga Lampek; Pongrác Ács; Márta Hock (BMC, 2020)
Abstract Background It is well known that physical activity (PA) has health benefits. This study aimed to examine physical activity carried out by the senior (over 50) participants and its relation to their quality of life (QoL). Methods Surveillance of PA and QoL was measured by using questionnaires (GPAQ, WHOQoL-BREF) in this study. Descriptive data were presented as means and standard deviations (SD) for continuous variables and as percentages for categorical variables. Multivariate linear regression analysis was conducted. The significance level was set at p ≤ 0.05. Results Overall, 250 participants were recruited, the mean age of the study population (n = 243) was 70.2 (SD 7.1) years. The results clearly showed that the Hungarian participants aged over 50 years were more likely to do PA if they had university degree and lower age (p ≤ 0.001) and used more active transportation (p = 0.035) if they had low education. The results of WHOQoL-BREF showed that the Hungarian individuals have better QoL if they have university degree (p ≤ 0.001) and lower age (p ≤ 0.001). Using multivariate linear regression analysis to examine the effect of PA patterns on QoL adjusted for demographic variables (age, education, BMI, place of living), the result showed significant correlation between WHOQoL-BREF dimensions and GPAQ (p ≤ 0.001). Conclusion Higher amount of PA among aging population can result in better QoL in all dimensions.